What are Palliative Care Physicians for Adults Taught on Palliative Care for Children? Paediatric Aspects in Palliative Care Curricula for Adults - Schiessl, C.; Gottschling, S.; Gronwald, B. M. (Klinische Pädiatrie, 2016)
Background: Children suffering from life limiting diseases are frequently cared for by adult palliative care teams due to missing paediatric structures in that field. However it is questionable whether palliative care curricula for physicians comprehensively cover issues of paediatric palliative care (PaedPC).Aim: To identify all PaedPC issues included in inter-professional or medical palliative care curricula (PCC) and to evaluate the breadth and quality of PaedPC issues covered in these curricula.Design: Inter-professional or medical palliative care curricula (PCC) were identified by an extensive literature review in German and English using the search-engines Google as well as Medline, MedPilot and Pubmed.Results: Worldwide 30 PCC were identified, with only 15 curricula mentioning any PaedPC issues. Of those 15 curricula, up to 22 PaedPC topics were highlighted in each. In 10 or more PaedPC following topics were highlighted: grief and bereavement in family, parents and siblings; communication with children; paediatric malignancies; pain management in PPC and pharmacology. In the majority of PCC curricula where PaedPC issues were identified the following topics were mentioned- grief and bereavement in the family, parents and siblings, communication with children, paediatric malignancies, paediatric pain management and pharmacology.Conclusions: The variability of inclusion of PaedPC issues and the lack of depth and standardisation of knowledge, skills and attitudes in PaedPC issues included in PCC curricula is not sufficient to guide adult palliative care physicians in their clinical work with children suffering from life limiting diseases.
Keywords: palliative Care; end-of-life-care; curriculum; postgraduate education